Factors influencing pre-marital sexual intercourse among unmarried young individuals in Cambodia - Mai, Vanthy; Kittisuksathit, Sirinan (Makara Journal of Health Research, 2019)
Background: Sexual behavior of young individual are recognized as one of the main health priority in society. In Cambodia, young individual who hasten to involve in sexual intercourse, contributes to their high risk of various health issues, particularly those related to sexual reproductive health. This research will identify specific characteristics that have strong relationships with pre-marital sexual intercourse among unmarried young individuals in Cambodia. Methods: A binary logistic regression in a multivariate analysis of secondary data was applied from the 2014 cambodian demographic and health survey. the data about pre-marital sexual intercourse were assessed with the CDHS questionnaire including as age, sex, education, place of resident, risky behavior, living arrangement, and exposure to mass media, knowledge about sexual and reproductive health and HIV prevention. Results: age (p = 0.000), sex (p = 0.000), place of residence (p = 0.000), staying away experience (p = 0.001), and smoking behavior (p = 0.000), were significantly associated with pre-marital sexual intercourse among unmarried young individuals. Conclusion: Appropriate reproductive health promotion programs and disease prevention strategies must be organized for target groups of young individuals who engage in pre-marital sexual intercourse. Moreover, comprehensive reproductive health education should be disseminated to increase awareness of risky sexual behavior and allow young individuals to make informed decisions regarding their sexual practices.